2021
DOI: 10.1155/2021/9361348
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Intrusion Detection Based on Federated Learning for Edge-Assisted Internet of Things

Abstract: As an innovative strategy, edge computing has been considered a viable option to address the limitations of cloud computing in supporting the Internet-of-Things applications. However, due to the instability of the network and the increase of the attack surfaces, the security in edge-assisted IoT needs to be better guaranteed. In this paper, we propose an intelligent intrusion detection mechanism, FedACNN, which completes the intrusion detection task by assisting the deep learning model CNN through the federate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…For validation purposes, authors use a dataset containing traffic of a single IoT protocol. Moreover, recently a federated version of CNN was used by [28] for intrusion detection in IoT that is intended to reduce communication overhead. Other works, such as [29], are based on old industrial datasets that do not consider recent attacks from IIoT scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…For validation purposes, authors use a dataset containing traffic of a single IoT protocol. Moreover, recently a federated version of CNN was used by [28] for intrusion detection in IoT that is intended to reduce communication overhead. Other works, such as [29], are based on old industrial datasets that do not consider recent attacks from IIoT scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…Chatterjee et al [103] proposes a Probabilistic Hybrid Ensemble Classification (PHEC) model in the centralized and federated mode The study revealed that, compared with these modes, the FL mode performs better regarding privacy issues of the data and the problem of data processing in a single system. Man et al [104], presented a FEDACNN model based on CNN to solve the communication delay issue in the system by reducing communication rounds to 50%. Rajendran et al [105] proposed two FL models with ANN and LR for patient data privacy and security in healthcare systems.…”
Section: Federated Placement Ids For Iot Systemsmentioning
confidence: 99%
“…Furthermore, it neglects unimportant parameter transmissions to the server with the help of an attention mechanism and greatly enhances the security performance with minimum communication overhead. The authors of [ 24 ] presented a federated-learning-assisted intelligent IDS model that exploits the FedACNN algorithm to detect intrusions in edge-enabled industrial IoT environments. It solves the issues associated with centralised machine learning models by transferring model parameters to the global server with high security instead of sending raw data.…”
Section: Related Workmentioning
confidence: 99%